Community Participation in The Development Plan of Pelaihari Sub-District, Tanah Laut District in 2021 - Raisha Dewina Sari; Mahyuni Mahyuni; Taharuddin Taharuddin (PT Mattawang Mediatama Solution, 2023)
Community involvement plays a crucial role in the process of development planning, which is a crucial stage in the overall development process. This process involves analyzing the needs and issues in the field and seeking recommendations for solutions that will be outlined in the form of planning documents. However, based on the results of the data analysis in the field, community participation in development planning in Pelaihari Village in 2021 is still low, as demonstrated by the lack of attendance of community representatives and the inadequate presence of resource persons. Besides, there need to be more proposals for the process of development planning consensus (Musrenbang). This study aims to investigate the reasons for the lack of community involvement in Pelaihari Village's development planning in 2021. Explanatory qualitative research methods are used in this study to gather information from sources including the Sub-District Heads of Pelaihari Village, a representative of the neighborhood head in Pelaihari Village, the head of Pelaihari District, and the head of the Tanah Laut Regency Development Planning Department. The findings of the field study on the reasons for low community involvement in development planning in Pelaihari Village in 2021 show that the first factor is the mindset of the people who still do not trust and understand the process of development planning and the benefits of their participation in it. The second is the technical factor of implementation which is still not optimal and not suitable for urban areas, and the last is the Pelaihari sub-district heads' lack of initiative in gathering information to share with the community and their lack of creativity in planning technological implementation and engaging the community. Finally, the recommendations in this study are directed at the Tanah Laut District Government, the Pelaihari District Head, and the Pelaihari Sub-District Head. They include improving technical implementation, changing community attitudes through socialization, and boosting village head initiatives and innovations